2005
DOI: 10.1021/ol052341t
|View full text |Cite
|
Sign up to set email alerts
|

Cholic-Acid-Based Fluorescent Sensor for Dicarboxylates and Acidic Amino Acids in Aqueous Solutions

Abstract: [structure: see text] The binding affinities of a cholic-acid-based fluorescent neutral receptor toward dicarboxylate anions and amino acids have been investigated in a CH3OH/H2O system (1:1, 0.01 M HEPES buffer, pH = 7.4) by fluorescence titration experiments. The synthetic host bearing four convergent functionalities strongly binds glutamate via multiple hydrogen bonds with a binding constant of (5.57 +/- 0.88) x 10(6).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
22
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 123 publications
(22 citation statements)
references
References 29 publications
0
22
0
Order By: Relevance
“…A wide variety of host receptors have been reported that can effectively bind anions in solution and in the solid states, exhibiting selectivity toward certain anions 4 7 . In this regard, carboxylates are of great interest due to their important roles in chemistry and biology 8 10 . Several multi-carboxylates including citrate, succinate, malate, and fumarate are critical chemical species in living cells that are involved in the Krebs cycle to generate energy used by aerobic cells in humans 11 .…”
Section: Introductionmentioning
confidence: 99%
“…A wide variety of host receptors have been reported that can effectively bind anions in solution and in the solid states, exhibiting selectivity toward certain anions 4 7 . In this regard, carboxylates are of great interest due to their important roles in chemistry and biology 8 10 . Several multi-carboxylates including citrate, succinate, malate, and fumarate are critical chemical species in living cells that are involved in the Krebs cycle to generate energy used by aerobic cells in humans 11 .…”
Section: Introductionmentioning
confidence: 99%
“…Dicarboxylates (DC 2− ) constitute a large and structurally diverse class of anions that play crucial roles in biology and industry, with some implicated as environmental pollutants (e.g., oxalate) . Their biological importance has primarily driven the design and development of polytopic abiotic receptors that utilise hydrogen bonding (HB) interactions and Lewis acidic metal centres for binding and sensing . However, DC 2− are highly challenging targets for selective recognition because of their hydrophilicity and complex overall shapes, which arise from the diversity of spacer motifs between their anionic carboxylate termini.…”
Section: Figurementioning
confidence: 99%
“…The thiourea compounds were recognized to possess some industrial applications in the fields of catalysis, as inhibitors and removal of some toxic metals . Thioureas have ability to form promising building blocks for the selective recognition and detection of anions via the H‐ bond active sites . For example, pyridyl thioureas showed unexpectedly sensing properties towards carboxylate over halides and vice versa upon the protonation .…”
Section: Introductionmentioning
confidence: 99%